Shocks, vulnerability and income generating capacity of rural households: Evidence from Southeast Asia - Dorothee Bühler; Wendy Cunningham (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
Against the background of rising weather risks this paper seeks to understand how risks impact the income generating capacity of rural households in Southeast Asia. In this study, we use assets to predict households' income generating capacity and examine the role of different shock categories on asset accumulation. In addition, we detect region, country and income group specific patterns. We use panel data from Cambodia, Laos, Thailand, and Vietnam covering 5,200 rural households. Households' income generating capacity is estimated in a fixed-effects regression based on assets owned or accessed by the household. The findings suggest that shocks decrease the asset accumulation rate of rural households by 1.4 percentage points across all four countries. While health shocks decrease households' asset accumulation rate by 1.2 to 1.4 percentage points, the effect of drought and flood shocks is twice as high. At the country level, the effect of flood shocks on asset growth are strongest in Vietnam while drought shocks disproportionately affect Laotian households. Households are largely able to anticipate the occurrence of health shocks, while droughts and floods are less predictable and thus, have a more detrimental effect on asset growth. The effects of shocks differ across income quartiles. While households in the richest quartile are able cope with weather shocks, health shocks affect their asset accumulation disproportionately. Poor households are strongest affected by drought shocks.
Keywords: I32; O18; Q1; 330; Shocks; Asset-based approach; Economic development; Poverty; Regional analysis; Southeast Asia